Leukocyte infiltration of cremaster muscle inmice assessed by intravital microscopy - Kranig, Simon A.; Lajqi, Trim; Tschada, Raphaela; Jungwirth, Maylis; Kuß, Navina; Pöschl, Johannes; Hudalla, Hannes (JoVE. Video journal, 2020)
Intravital microscopy (IVM) is widely used to monitor physiological and pathophysiological processes within the leukocyte recruitment cascade in vivo. The current protocol represents a practical and reproducible method to visualize the leukocyte endothelium interaction leading to leukocyte recruitment in skeletal muscle derived tissue within the intact organism of the mouse. The model is applicable to all fields of research that focus on granulocyte activation and their role in disease. We provide a step by step protocol to guide through the method and to highlight potential pitfalls and technical difficulties. The protocol covers the following aspects: experimental settings and required material, anesthesia of the mouse, dissection of the cremaster muscle as well as tracheal and carotid cannulation, IVM recordings and offline analysis. Data formats like adherent leukocytes, rolling flux (RF) and rolling flux fraction (RFF) are explained in detail and appropriate applications are discussed. Representative results from dystrophin deficient mdx mice are provided in the results section. IVM is a powerful tool to assess leukocyte recruitment in an in vivo setting; however, delineating for example endothelial and leukocyte function may require a combination with ex vivo setups like flow chamber experiments. Furthermore, the genetic background of animals of interest may greatly influence baseline recruitment, requiring individual fine tuning of the protocol provided. Despite its limitations, IVM may serve as a platform to readily translate in vitro findings into a living vertebrate organism.
Gesehen am 27.05.2020
Enthält auch Textversion
Wissenschaftlicher Film. Deutschland. 2020
Keywords: Film